Contained-Reflected Megaturbidites of the Marnoso-arenacea Formation (Contessa Key Bed) and Helminthoid Flysches (Northern Apennines, Italy) and Hecho Group (South-Western Pyrenees) - Tinterri, Roberto; Mazza, Tommaso; Magalhaes, Pierre Muzzi (Frontiers in Earth Science, 2022)
Contained-reflected beds deposited by fully-ponded or partially-reflected turbidity currents are important because their correct evaluation can give important indications on the degree of basin confinement and on the type, size and orientation of the morphological obstacle. Through a detailed facies analysis of various significant megabeds in the Marnoso-arenacea Formation, including the Contessa key bed, in the helminthoid flysches in the northern Apennines (Italy) and in the Pyrenees (megaturbidite MT5), this work proposes a depositional model that is well consistent with the recent experimental data available in the literature, discussing their strengths and limits. The Contessa and flysch megabeds fit very well with the experimental conditions because they are deposited in narrow and elongated confined basins characterized by axial flows. Indeed, in the proposed model, it is possible to recognize facies deposited by: 1) a basal underflow directed towards the bounding slope (Facies A), 2) an intermediate part of the flow characterized by lateral deflections (facies B1), 3) an upper well-developed reversing flow (facies B2) and 4) an uppermost residual reversing flow recording the final collapse of the fine-grained suspended load forming a poorly-sorted slurry facies C and a very thick mudstone unit D. Facies A, B1 and B2 are usually separated by very thin fine-grained muddy drapes rich in carbonaceous matter, which can be traced throughout the basin. These drapes - very common in contained and confined beds in these settings - can be related to internal density surfaces, along which decoupling processes, separating underflows from reversing overflows, can easily occur. Conversely, as the MT5 is characterized by a source transversal to an elongated narrow basin, the large flow volume versus basin capacity hinders the generation of reversing flows and rebound layers favouring the formation of fully-ponded pulsating overflows able to deposit alternations of laminated and massive units. This facies type can be observed in the basins that are characterized by axial flows only near the basin margins where the pulsating collapse of the reversing flow can dominate. This study shows that the integration of detailed field studies are essential to validate experimental data from an applicative point of view.